2021
DOI: 10.1590/1414-431x20209422
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil of Hyptis crenata Pohl ex Benth. presents an antiedematogenic effect in mice

Abstract: Hyptis crenata , commonly known as “salva-do-Marajó”, “hortelã-do-campo”, and “hortelãzinha”, is used in folk medicine in Northeast Brazil as tea or infusion to treat inflammatory diseases. Due to the pharmacological efficacy and the low toxicity of the essential oil of Hyptis crenata (EOHc), we decided to investigate the EOHc antiedematogenic effect in experimental models of inflammation. EOHc was administrated orally at doses of 10-300 mg/kg to male Swiss albino mice. Paw ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Coelho-de-Souza et al. (2021) also demonstrated that the essential oil of H. crenata has an anti-edematogenic effect in different models of paw edema, attributing these actions to the presence of 1,8-cineole [40] .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Coelho-de-Souza et al. (2021) also demonstrated that the essential oil of H. crenata has an anti-edematogenic effect in different models of paw edema, attributing these actions to the presence of 1,8-cineole [40] .…”
Section: Resultsmentioning
confidence: 98%
“…In this context, in the Lamiaceae family, there are a plethora of species with rich content in essential oils, which are used in popular medicine as an alternative treatment for diseases [2] . For example, the genus Hyptis is considered of great economic importance since it is composed of triterpenes [3] , diterpenes [4] and sesquiterpenes [5] , that are responsible for interesting antimicrobial [ 6 , 7 ], insecticide [8] , analgesic [9] , [10] , [11] , and hypnotic-sedative and antipsychotic-like activity [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The edible, scented and functional properties of M. officinalis make it a plant of choice for application in food and pharmaceutical industries. M. officinalis extract is medicinal and most countries use it in their traditional systems of medicine to treat many diseases [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The edible, scented and functional properties of M. officinalis make it a plant of choice for application in food and pharmaceutical industries. M. officinalis extract is medicinal and most countries use it in their traditional systems of medicine to treat many diseases [8][9][10][11][12][13]. In Algeria, M. officinalis is used as integrated pharmaceutical treatment option for the treatment of headache, indigestion, abdominal cramps, heart failure, diabetes and bacterial viral infections [1,14].…”
Section: Introductionmentioning
confidence: 99%